Accumulation of a lipid-linked intermediate involved in enterobacterial common antigen synthesis in Salmonella typhimurium mutants lacking dTDP-glucose pyrophosphorylase. - Rick, P D (1988)
The heteropolysaccharide chains of enterobacterial common antigen (ECA) are composed of linear trisaccharide repeat units having the structure----3)-alpha-Fuc4NAc-(1----4)-beta-D-ManNAcA-(1---- 4)-alpha-D-GlcNAc- (1----. Mutants of Salmonella typhimurium lacking the structural gene for dTDP-glucose pyrophosphorylase (rfbA) are severely impaired in their ability to synthesize dTDP-glucose, which is a precursor of dTDP-4-acetamido-4,6-dideoxy-D-galactose (Fuc4NAc), the donor of Fuc4NAc residues for ECA synthesis. These mutants synthesize only trace amounts of ECA, and they are hypersensitive to sodium dodecyl sulfate (SDS). Incubation of delta rfbA mutants with [3H]N-acetylglucosamine ([3H]GlcNAc) resulted in the accumulation of radioactivity in N-acetyl-D-mannosaminuronic acid (ManNAcA)-GlcNAc-pyrophosphorylundecaprenol (lipid II), the putative acceptor of Fuc4NAc residues in ECA synthesis. Lipid II did not accumulate in either wild-type cells or in rff mutants unable to synthesize ManNAcA. Both the accumulation of lipid II and the synthesis of trace amounts of ECA were abolished when delta rfbA mutants were grown in the presence of the antibiotic tunicamycin. Tunicamycin also prevented the SDS-mediated lysis of the mutants. SDS-resistant derivatives of delta rfbA mutants were isolated that were no longer able to synthesize trace amounts of ECA. Characterization of these derivatives revealed that they were defective in various steps of ECA synthesis leading to the synthesis of lipid II. The data support the conclusion that accumulation of lipid II is responsible in some way for the hypersensitivity of delta rfbA mutants to SDS.